Noninvasive monitoring of infection and rejection after lung transplantation - De Vlaminck, Iwijn (Proc Natl Acad Sci U S A, 2015)
The survival rate following lung transplantation is among the lowest of all solid-organ transplants, and current diagnostic tests often fail to distinguish between infection and rejection, the two primary posttransplant clinical complications. We describe a diagnostic assay that simultaneously monitors for rejection and infection in lung transplant recipients by sequencing of cell-free DNA (cfDNA) in plasma. We determined that the levels of donor-derived cfDNA directly correlate with the results of invasive tests of rejection (area under the curve 0.9). We also analyzed the nonhuman cfDNA as a hypothesis-free approach to test for infections. Cytomegalovirus is most frequently assayed clinically, and the levels of CMV-derived sequences in cfDNA are consistent with clinical results. We furthermore show that hypothesis-free monitoring for pathogens using cfDNA reveals undiagnosed cases of infection, and that certain infectious pathogens such as human herpesvirus (HHV) 6, HHV-7, and adenovirus, which are not often tested clinically, occur with high frequency in this cohort.